Agrobiodiversity index for supporting public and private sector decision-making on biodiversity in food systems, for healthy diets, sustainable production, and conservation - CGIAR Research Program on Water, Land and Ecosystems (2020)
Uptake by private sector users including Wholechain and OLam - see OICR in MARLO (Evidence section in the menu)